Respuesta :

Step-by-step explanation:

f(4)= -3(4)-1= -13

g(-2)= -2(-2)^3 -3

=16-3 =13

Answer:

[tex]f(4) = \boxed{-13}[/tex]

[tex]g(-2) = \boxed{13}[/tex]

Step-by-step explanation:

Given functions:

[tex]\begin{cases}f(x)=-3x-1\\g(x)=-2x^3-3 \end{cases}[/tex]

To find f(4), substitute x = 4 into function f(x):

[tex]\begin{aligned}f(4) & = -3(4)-1\\& = -12-1\\& = -13\end{aligned}[/tex]

To find g(-2), substitute x = -2 into function g(x):

[tex]\begin{aligned}g(-2) & = -2(-2)^3-3\\& = -2(-8)-3\\& = 16-3\\& = 13\end{aligned}[/tex]

Therefore:

[tex]f(4) = \boxed{-13}[/tex]

[tex]g(-2) = \boxed{13}[/tex]

ACCESS MORE